Plant organic farming research – current status and opportunities for future development. Issue 2 (4th March 2018) - Tsvetkov, Ivan; Atanassov, Atanas; Vlahova, Mariana; Carlier, Lucien; Christov, Nikolai; Lefort, Francois; Rusanov, Krasimir; Badjakov, Ilian; Dincheva, Ivayla; Tchamitchian, Mark; Rakleova, Goritsa; Georgieva, Liliya; et al.
ABSTRACT: This paper reviews the recent development of the scientific, legislative, economic and environmental aspects of plant organic farming. The impact of organic farming on biodiversity and soil fertility is discussed in comparison with conventional systems. A significant barrier for wide application and future development of organic farming is the existing diversity of national and international policy instruments in this sector. Special attention is paid to up-to-date research techniques that could help solve a number of the problems typically faced in plant organic farming. It is argued that organic farming is still not productive enough to be considered fully sustainable. This underlines the necessity of strong support for more effective implementation of scientific research innovations and improvement of the networking between all stakeholders – organic producers, scientists and corresponding policy makers at the national and international level.